2013
DOI: 10.1007/s11892-012-0359-3
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Community Health Workers in Diabetes: Update on Current Literature

Abstract: Community health worker (CHW) interventions have been found to be a promising strategy for improving diabetes outcomes, especially among low-income and racial and ethnic minority populations. This review serves as an update of the literature published since 2011 on CHWs’ role in diabetes care. In our review of the most current literature, we noted several key areas of advancement. These areas include community-based participatory research (CBPR) approaches to intervention development and evaluation, analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 27 publications
(25 reference statements)
0
100
0
Order By: Relevance
“…Of 16 studies reviewed, investigators noted that significant reductions in hemoglobin A1C values were reported in eight studies. A recent review of literature published in 2011 and 2012 assessing the evidence emerging from community-based participatory research approaches involving CHWs provided evidence of improved glycemic control or reduced risk of disease progression (2,3,7,19,43,60,61,111,116,127). Cancer screening.…”
Section: Evidence For Community Health Worker Effectiveness In the Unmentioning
confidence: 99%
“…Of 16 studies reviewed, investigators noted that significant reductions in hemoglobin A1C values were reported in eight studies. A recent review of literature published in 2011 and 2012 assessing the evidence emerging from community-based participatory research approaches involving CHWs provided evidence of improved glycemic control or reduced risk of disease progression (2,3,7,19,43,60,61,111,116,127). Cancer screening.…”
Section: Evidence For Community Health Worker Effectiveness In the Unmentioning
confidence: 99%
“…[1][2][3] As value-based payment models expand, providers will have more flexibility to fund CHWs with global budgets, or payers may elect to reimburse for CHW services. [4][5][6] The emerging evidence base on CHW programs 7 for the prevention and management of chronic diseases includes systematic reviews concluding that CHW interventions can improve overall health outcomes 8 and outcomes for patients with heart disease, stroke, 9 type II diabetes, [10][11][12] HIV, 13 and asthma 2,14 and for vulnerable patients with or at risk for a variety of chronic diseases or cancer. 15 Other systematic reviews have also documented the costs and cost-effectiveness of CHW programs, 15 but none, outside of low and middle-income countries, 16 have examined the impact of CHWs on the utilization of health services by patients with chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Health care community linkages are receiving increasing attention from the American Medical Association, the Agency for Healthcare Research and Quality, and others as a means of promoting translation of clinical recommendations for lifestyle modification in real-world settings (69). Community health workers (CHWs) (70), peer supporters (71,72), and lay leaders (73) may assist in the delivery of DSMES services (61), particularly in underserved communities. A CHW is defined by the American Public Health Association as a "frontline public health worker who is a trusted member of and/or has an unusually close understanding of the community served" (74).…”
Section: Community Supportmentioning
confidence: 99%